Steering in Video-Based Driving Simulation with Stereo Depth Maps: Dynamic Perspective Corrections. Issue 1 (January 2015) - Brogan, Michael; Markham, Charles; Commins, Sean; Deegan, Catherine
This paper describes a video-based driving simulator that allows the user to steer through a video sequence acquired by a mobile mapping system. This mapping system acquired geotagged stereo video at a rate of 10 Hz. The video data were collected from a standard vehicle, which was driven along a road under normal road conditions. With the use of the stereo image data, a method that allowed a participant to steer through a video was implemented. An experiment to assess a driver's response to this steering is presented. Drivers were found to respond to the geometry of the video sequence by steering left or right when expected.